Manufacturing of high-quality green CSA-supported OPC cement with optimum physical and mechanical properties - Hala A. Hossein; Bassem S. Nabawy; Samah A. Sanad; E. A. El-Alfi (Scientific Reports)
Abstract In the current study, we aim to enhance the physical and mechanical properties of the ordinary Portland cement (OPC) by incorporating small amounts of calcium sulfoaluminate (CSA) at a rate of 0, 1, 2 and 3% (mixtures A, B, C, and D) to improve its physical and mechanical properties. These mixtures allowed the CSA clinker to emit less CO2 and clink at a low temperature of 1250 °C, which is significantly lower than that of the OPC clinker (1450 °C). The apparent density, specific gravity, porosity, and unconfined compressive strength (UCS) of the pure OPC (0%, mixture A) and the OPC-CSA pastes (B, C, & D mixtures) were measured at curing periods of 1, 3, 7, 28, and 90 days. The scanning electron microscopy (SEM) coupled with the energy dispersive X-ray (EDS) was employed to investigate the internal structure of these pastes, while the XRF technique was employed to determine their chemical composition. Additionally, the optical characteristics of the formulated and disintegrated phases were delineated using FTIR spectroscopy, while the differential thermal analysis (DTA) and thermogravimetric analysis (TGA) were employed to examine them as the curing age increased. The mixture C (2% CSA + 98% OPC) sintered at 90 days is characterized by the best physical and mechanical properties (compressive strength = 52.5 MPa, porosity = 2.86%, apparent density = 2.015 g/cc, and specific gravity = 2.405 g/cc). This procedure is beneficial on a laboratory scale and applicable on the industrial scale to improve the physical and mechanical characteristics of the OPC and decrease its energy consumption.